Piperidinium derivatives including spectaline and cassine derivatives, pharmaceutic compositions containing the same and preparation process - Viegas Junior, Cláudio; Bolzani, Vanderlan da Silva [UNESP]; Barreiro, Eliezer Jesus de Lacerda; Castro, Newton G.; Young, Maria Claudia Marx; Rocha, Monica Santos; Fraga, Carlos Alberto Manssour (Instituto Nacional de Propriedade Industrial (INPI), 2010)
Disclosed are compounds of formulae (II) and (III), wherein R1 is other than hydrogen and the remaining substituents are as defined in the specification, processes for their preparation and pharmaceutical compositions containing them. The compounds are capable of inhibiting acetylcholinesterase, and are useful in the treatment of pathologies associated with cholinergic transmission, such as memory related disorders, neurodegenerative disorders such as Alzheimer's Disease, Myasthenia Gravis and intoxication induced by chemical agents.
Processo: NZ554392A
Número de publicação: NZ554392 (A)
Número de aplicação: NZ20040554392